2022
DOI: 10.1002/ejoc.202201113
|View full text |Cite
|
Sign up to set email alerts
|

Rh(III)‐Catalyzed Oxidative Annulation of 2‐Aryl‐1H‐benzo[d]imidazoles with 1,4‐Quinones through C−H Activation

Abstract: Rh(III) catalyzed oxidative annulation of 2-aryl-1Hbenzo[d]imidazoles with 1,4-quinones has been achieved for the synthesis of a novel class of benzo[4,5]imidazo[1,2f]phenanthridine-1,4-dione frameworks through a sequential CÀ C and CÀ N bond formations in a single-step operation. This is the first report on the oxidative annulation of 2-aryl-1Hbenzo[d]imidazoles with 1,4-quinones to produce highly functionalized phenanthridine-1,4-dione derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…12 In recent years, benzoquinones and 1,4-naphthoquinones have emerged as competent coupling partners in transition-metal-catalyzed C−H functionalization reactions, 13 but their reaction with 2-alkenyl/2-arylimidazoles has been rarely explored. 14 Thus, we examined the annulation reaction of 1,4-naphthoquinone (6a) with 4a in the presence of Ru catalyst. A preliminary investigation revealed that the reaction of 4a and 6a in the presence of [Ru(p-cymene)Cl 2 ] 2 , Cu(OAc) 2 , AgSbF 6 , and AcOH in DMA at 140 °C for 4 h produced 7aa in 73% yield.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 In recent years, benzoquinones and 1,4-naphthoquinones have emerged as competent coupling partners in transition-metal-catalyzed C−H functionalization reactions, 13 but their reaction with 2-alkenyl/2-arylimidazoles has been rarely explored. 14 Thus, we examined the annulation reaction of 1,4-naphthoquinone (6a) with 4a in the presence of Ru catalyst. A preliminary investigation revealed that the reaction of 4a and 6a in the presence of [Ru(p-cymene)Cl 2 ] 2 , Cu(OAc) 2 , AgSbF 6 , and AcOH in DMA at 140 °C for 4 h produced 7aa in 73% yield.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The high therapeutic potential and unique reactivity of the naphthoquinones make them attractive for the development of new type of compounds . In recent years, benzoquinones and 1,4-naphthoquinones have emerged as competent coupling partners in transition-metal-catalyzed C–H functionalization reactions, but their reaction with 2-alkenyl/2-arylimidazoles has been rarely explored . Thus, we examined the annulation reaction of 1,4-naphthoquinone ( 6a ) with 4a in the presence of Ru catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Further, in 2022, Reddy and co‐workers have unraveled an Rh(III)‐catalyzed oxidative annulation of differently substituted benzoimidazoles with 1,4‐quinones via the C−H activation process for synthesizing the benzoimidazophenanthridine‐1,4‐dione frameworks through a successive carbon‐carbon and carbon‐nitrogen bond formations in a one‐pot reaction (Scheme 38). [87] Mechanistically, a monomeric cationic form of rhodium catalyst was formed in situ from the dimeric [Cp*RhCl 2 ] 2 complexes, and in the combination of Cu(OAc) 2 , it generated an active catalyst [RhCp*(OAc) 2 ], which is highly reactive toward the activation of ortho −C−H bond of the arene, rhodium metal is stabilized by coordination with a N‐atom of benzoimidazole by forming a five‐membered metallocycle I . Further, π‐complexation with 1,4‐quinone facilitates the formation of ternary complex II .…”
Section: Direct Functionalization Of Quinonesmentioning
confidence: 99%